Spatiotemporal dynamics and driving factors of energy-related carbon emissions in the Yangtze River Delta region based on nighttime light data - Huazhu Xue; Qianqian Ma; Xiaosan Ge (Scientific Reports)
Abstract Owing to China’s massive area and vastly differing regional variations in the types and efficiency of energy, the spatiotemporal distributions of regional carbon emissions (CE) vary widely. Regional CE study is becoming more crucial for determining the future course of sustainable development worldwide. In this work, two types of nighttime light data were integrated to expand the study’s temporal coverage. On this basis, the distribution of energy-related CE in the Yangtze River Delta (YRD) region of China was estimated at a multispatial scale. Then the spatiotemporal dynamics of CE were explored based on the estimated results. The findings showed that the growth rate of CE in the YRD displayed three stages, and the total CE fluctuated upward. The spatial pattern of CE demonstrated a step-like decline from east to west. However, the Gini coefficient indicated that the differences in CE between cities gradually decreased since the CE had a strong spatial positive correlation in the YRD. Multiple factors affected the spatial variation of CE in the YRD, with economic level and population as the “critical” influencing elements, which determined the absolute amount of CE. This study provides a long-term analysis of CE dynamics while enhancing explanatory accuracy. The methods offer novel perspectives and tools for regional CE research. The results reveal spatial heterogeneity and clustering patterns of CE within regions, contributing valuable scientific evidence for monitoring regional CE and formulating emission reduction policies.